Norway : 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that the Norwegian economy performed well in 2014 despite the sharp fall in oil prices toward the end of the year. Mainland GDP grew at 2.2 percent, with weaker investment demand being offset by stronger government consumption. Unemployment stayed at a low level in 2014, but has recently edged up to 4.5 percent in June 2015 according to the labor force survey. The near-term outlook has weakened owing to lower oil prices. Mainland GDP growth is projected to slow to 1.3 percent in 2015 with weaker private investment and consumption. Looking further ahead, the medium and longer term present challenges of managing a transition away from the oil-dependent growth model.